Development of the application of information support of medical diagnostic and treatment centers - Milanov, M.; Leshchenko, Yu.; Yelizieva, A.; Artiukh, R. (Національний технічний університет "Харківський політехнічний інститут", 2020)
The subject of the article's research is the model and technology of information support for the medical diagnostic and treatment center (MDTC). The goal is to reduce costs and the time to organize the work a medical diagnostic and treatment center by applying and developed models and an information system. The following problems were solved in the paper: to conduct an analytical review of existing integrated medical information systems; to develop a model for the functioning of the MDTC; to develop software for the subsystem of information support for the MDTC functioning, including the local drug formulary. Methods of the theory of algorithms, automaton models and technologies for software applications development were used to solve these problems. The following results were obtained. Existing medical systems that allow automating the business processes of medical institutions are analyzed, their advantages and disadvantages are designated. The functional subsystems of the MDTC that automate the functions of the departments of a medical institution are designated. Automation models and expressions of the algebra of relationships have been obtained for the main departments of the MDTC, that allow to present in a formalized form the process of a medical institution functioning. The model of the functioning of the MDTC is formed on the basis of the theory of automate and an expression of the algebra of relations is obtained that describes in a formalized form the work of the medical center. The structure of the software system for information support of the MDTC is proposed. The navigation system of the web-resource of MDTC was developed. A use-case diagram was developed showing the functionality of the main categories of users. Conclusions: the information support of the MDTC will reduce the time for patient care due to the organized sequence of actions of department staff and reduce the risk of errors in diagnosis due to mathematical and statistical processing of the results of the diagnostics. A drug formulary was developed, which allows the patient to receive recommendations on the use of drugs based on the entered search parameters.

Предметом дослідження статті є моделі і технології інформаційної підтримки медичного лікувально діагностичного центру (МЛДЦ). Метою є зниження витрат і скорочення часу на організацію роботи медичного лікувально-діагностичного центру, шляхом застосування розроблених моделей та інформаційної системи. В роботі вирішуються наступні задачі: проведення аналітичного огляду існуючих інтегрованих медичних інформаційних систем; розробка моделі функціонування МЛДЦ; розробка програмного забезпечення для підсистеми інформаційної підтримки функціонування МЛДЦ, включаючи локальний формуляр лікарських препаратів. Для вирішення зазначених завдань були використані методи теорії алгоритмів, автоматних моделей, технології розробки програмних додатків. Отримані наступні результати. Проаналізовано існуючі медичні системи, які дозволяють автоматизувати бізнес-процеси лікувальних установ, виділені їх переваги та недоліки. Виділено функціональні підсистеми МЛДЦ, що автоматизують функції відділень медичного закладу. Для основних відділень МЛДЦ отримані автоматні моделі і вирази алгебри алгоритмів, що дозволяють представити в формалізованому вигляді процес функціонування медичного закладу. Сформована модель функціонування МЛДЦ на основі теорії автоматів і отримано вираз алгебри відносин, яке описує в формалізованої вигляді роботу медичного центру. Запропоновано структуру програмної системи інформаційної підтримки МЛДЦ. Розроблено навігаційна система web-ресурсу МЛДЦ. Розроблено діаграму прецедентів, що показує функціональні можливості основних категорій користувачів. Висновки: інформаційна підтримка МЛДЦ дозволить скоротити час на обслуговування пацієнтів за рахунок організованої послідовності дій співробітників відділів установи і скоротити ризик виникнення помилки при діагностиці за рахунок математико-статистичної обробки результатів проведення обстежень. Також розроблений формуляр лікарських препаратів, що дозволяє отримати пацієнтові рекомендації по використанню ліків на основі введених параметрів пошуку.
Розробка підсистеми інформаційної підтримки медичних лікувально-профілактичних центрів
Keywords: automation models; algebra of algorithms; information support system; case diagrams; web resources; drug formulary; автоматні моделі; алгебра алгоритмів; системи інформаційної підтримки; діаграми прецедентів; веб-ресурси; формуляри лікарських препаратів